Plan estratégico de marketing para el “Comercial Castro Andino y Compañia” de la ciudad de Loja - Castro Loaiza, Diego Fernando (2014)
The present study whose overall objective is to develop a "STRATEGIC MARKETING PLAN FOR COMMERCIAL CASTRO ANDES AND COMPANY OF THE CITY Loja" was developed in the city of Loja, in order to improve the economic and competitive microenterprise development, and the strategic marketing plan is an essential tool for any company that facilitates the sale of their products effectively. The methodology used in this research was in the first instance the synthetic Analytical method, which allowed us to analyze the object of study in its different parts and break until new knowledge; The Historical-Logical method used to collect the necessary information regarding the development of the project; The Inductive-Deductive Method is used it when addressing the necessary information on the marketing plan. The interview and survey were used to collect the information in a report on internal company data; with a sample of 274 surveys to internal customers of the company. Data obtained from the external analysis yielded results that allowed significant opportunities to know as "Accessibility technological means for companies" with a weight of 0.15 and Threats of relevance as "The company is located below the competition" with a weight of 0.20; with a total weight of 2.35 means that the threats are on opportunities. The internal analysis allowed to know that the most important strength is "exclusive provider of certain parts" with a weight of 0.15 and the most important weakness is that "No media used for advertising" with a weighting of 0.15: giving a weighted total of 2.65 prevailing strengths of weaknesses, which should be strengthened. EFE and IFE Matrix, some targets of strategic, product, price, advertising and parking, they have been developed as a proposed improvement to the marketing and positioning of the company were determined. Strategic objectives have; FO Strategy: Integrate the virtual technology system to spread the image of the company; DO Strategy: Implement a training plan for all staff to improve service and customer care; Strategy FA: Negotiating with new international and domestic providers to have the exclusivity of most products; Strategies DA: Disseminate the company, its products and services so that the image set their minds and delivers loyal customers. And expanding local design for better performance and development activities. Also as part of the proposed mission and business vision of a technical way, which conforms to reality and reflect the internal consensus of the organization defined; which must be objective, clear, and possible impulsadoras.campa meet.